Hubungan intensitas mengakses situs porno dengan perilaku seksual pranikah remaja - Aprita Yulia Lestari; Suherni Suherni; Yuni Kusrniyati (Poltekkes Kemenkes Yogyakarta, 2015)
ln Yogyakarta, 62,7% of adolescents are not a virgin, and there are 30% of the two million abortions porformed by adoloscents. Adolescents are in a situation that is very sensitive to the influence of the new value that can lead to deviant behavior. Pornography aims to stimulate one's sexual desire, so that their effects is the behavior that leads to an increase in adolescent sexual stimulation. Research conducted at internet cafe Glagahsari, Umbulharjo, Yogyakarta because there are intemet cafe in the area that has not installed non pornography filters. The aim of this study is to know the relationship between the intensity accessing pom sites withadolescent premarital sexual behavior in internet cafe Glagahsari, Umbulharjo, Yogyakarta. The type of research ia an observational with cross sectional approach. Sample size 60 adolescents aged 15-24 years were taken by purposive sampling technique. Data is a primary data were collected by questionnaire. Data were tested by Kendall Tau correlation test with alpha of 5%. Characteristics of respondents by age are mostly in the age group 15-19 years (70,8%), by sex mostly male (52,3%), based on most medium level of education (53,8%). lntensity accessing pom sites most rare (63,1%), adolescent premarital sexual behavior were mostly mild (49,2%). Corelation with the fest results obtained by Kendall Tau p-value of 0,000 means that there is a significant correlation between the intensity accessing porn sites with adolescents premarital sexual behavior. There is a positive relationship between theintensity accessing porn sites with adolescent premarital sexual behavior, which is more frequent aecess pomographic sites, the more severe premarital sexual behavior.